Coupled topology and shape optimization using an embedding domain discretization method - Stankiewicz, Gabriel; Dev, Chaitanya; Steinmann, Paul (Structural and Multidisciplinary Optimization, 2021)
Density-based topology optimization and node-based shape optimization are often used sequentially to generate production-ready designs. In this work, we address the challenge to couple density-based topology optimization and node-based shape optimization into a single optimization problem by using an embedding domain discretization technique. In our approach, a variable shape is explicitly represented by the boundary of an embedded body. Furthermore, the embedding domain in form of a structured mesh allows us to introduce a variable, pseudo-density field. In this way, we attempt to bring the advantages of both topology and shape optimization methods together and to provide an efficient way to design fine-tuned structures without predefined topological features.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Coupled topology and shape optimization; Embedding domain discretization; Structural optimization